The regime-dependent evolution of credibility: A fresh look at Hong Kong's linked exchange rate system - Boris Blagov; Michael Funke (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
An estimated Markov-switching DSGE modelling framework that allows for parameter shifts across regimes is employed to test the hypothesis of regime-dependent credibility of Hong Kong s linked exchange rate system. The model distinguishes two regimes with respect to the time-series properties of the risk premium. Regime-dependent impulse re- sponses to macroeconomic shocks reveal substantial differences in spreads. These findings contribute to efforts at modelling exchange rate regime credibility as a non-linear process with two distinct regimes.
Keywords: E32; F41; C51; 330